Understanding Patient Safety Culture: the Role of Sociodemographic Factors Among Nursing Students in Malaysia - Jamil, Noorsalfizah; Ramli, Shalinawati; Azmawati Mohamed, Nurul; Ismail, Zarini (Journal of Neonatal Surgery, 2025)
Patient safety is a fundamental component of healthcare systems, ensuring that individuals receive high-quality care without experiencing preventable harm. This study explores the sociodemographic characteristics of patient safety awareness among nursing students in private colleges. By examining key variables such as age, gender, educational background, clinical attachment experience, and formal training on patient safety, the study provides insights into how nursing students perceive and engage with patient safety protocols. The findings indicate that repeated exposure to clinical environments, structured patient safety training, and institutional policies play critical roles in shaping students' understanding of patient safety. The study also highlights the importance of fostering a strong safety culture within nursing education to enhance the overall quality of healthcare services.